Radiation-Induced Growth Retardation and Microstructural and Metabolite Abnormalities in the Hippocampus - Shaefali P. Rodgers; Janice A. Zawaski; Iman Sahnoune; J. Leigh Leasure; M. Waleed Gaber (Neural Plasticity)
Cranial radiotherapy (CRT) increases survival in pediatric brain-tumor patients but can cause deleterious effects. This study evaluates the acute and long-term impact of CRT delivered during childhood/adolescence on the brain and body using a rodent model. Rats received CRT, either 4 Gy fractions × 5 d (fractionated) or a cumulative dose of 20 Gy (single dose) at 28 d of age. Animals were euthanized 1 d, 5 d, or 3.5 mo after CRT. The 3.5 mo group was imaged prior to euthanasia. At 3.5 mo, we observed significant growth retardation in irradiated animals, versus controls, and the effects of single dose on brain and body weights were more severe than fractionated. Acutely single dose significantly reduced body weight but increased brain weight, whereas fractionation significantly reduced brain but not body weights, versus controls. CRT suppressed cell proliferation in the hippocampal subgranular zone acutely. Fractional anisotropy (FA) in the fimbria was significantly lower in the single dose versus controls. Hippocampal metabolite levels were significantly altered in the single dose animals, reflecting a heightened state of inflammation that was absent in the fractionated. Our findings indicate that despite the differences in severity between the doses they both demonstrated an effect on cell proliferation and growth retardation, important factors in pediatric CRT.